Pragmatisme Politik Nahdlatul Ulama Pada Masa Pemerintahan Presiden Joko Widodo - Aji Sakti Hidayatullah; Ahmad Chumeidi; Yusuf Fadli; Adie Dwiyanto Nurlukman (Faculty of Social and Political Sciences, Universitas Muhammadiyah Malang, 2022)
This study aims to explain the political pragmatism of Nahdlatul Ulama in Joko Widodo administration. As a socio-religious organization with a strong mass base, it can accompany NU's political fluctuations, both internally and externally. Many consider the political actions of Nahdlatul Ulama (NU) to be pragmatic. In a sense, NU's political actions were motivated by the motivation to gain status and power because they were very pro-government in the past and in recent years, especially during the reign of President Jokowi. To answer this problem, Ekowati's theory of political pragmatism is used which is then supported by James S. Coleman's rational choice theory. The data were collected through the literature contained in books, journals and other online sources that are representative and relevant and analyzed qualitatively using a literature approach. This study concludes that in theory it is true that NU has taken pragmatic steps in politics. However, on the other hand, NU does all of this in accordance with the existing Qoidah Fiqh, and indeed NU's politics has never really departed from the foundations contained in Fiqh.